Reading enjoyment amongst non-leisure readers can affect achievement in secondary school - Mol, Suzanne E.; Jolles, Jelle (Frontiers in Psychology, 2014)
This study aimed to evaluate determinants of differences in leisure reading behavior and school achievement. We specifically examined reading enjoyment, mental imagery, and sex as predictors in a large, age-homogeneous sample of Dutch secondary school students (N = 1,071). Results showed that the prevalence of leisure reading was low in both the lower, pre-vocational track (19.5%) and the higher, pre-academic track (32.5%). Boys read even less than girls. Almost all leisure readers enjoyed reading and engaged in mental imagery, i.e., the propensity ‘to see images’ of a written story in the mind’s eye. Overall, boys who did not like to read for leisure had the poorest school performance. Non-leisure readers who reported that they enjoyed reading got higher school grades in the higher educational track. In the lower track, this was the case for girls. Our study findings imply that reading promotion programs should take into account individual differences in sex, achievement level, and reading enjoyment when aiming to decrease the academic achievement gap.